Papillary Adenocarcinoma of the Extrahepatic Bile Duct in a Holstein Cow - Ilha, M. R. S. (2005)
A 15-year-old female Holstein cow was presented with a history of anorexia and weight loss. Abnormal physical examination findings included poor body condition, dehydration, icterus, and photodermatitis on nonpigmented areas of the skin of the dorsum. At necropsy, the common bile duct was greatly enlarged, with thickened walls, and tightly adhered to the hepatic capsular surface and serosa of adjacent loops of the small intestine. Two sessile, yellowish, friable, well-circumscribed, cauliflower-like, bulging masses (14 and 8 cm in diameter) were attached to the inner surface of the common bile duct blocking its lumen. Microscopically, the tumor was composed of well-differentiated, columnar epithelial cells with oval or round, vesicular, basal nuclei arranged in papillary projections. Periodic acid-Schiff-positive material accumulated in the apical cytoplasm of the neoplastic cells. Immunostaining of the tumor cells was positive for cytokeratin (CK) of wide-spectrum screening and for CK 7. The diagnosis of papillary adenocarcinoma of the extrahepatic bile duct was based on the morphologic features of the neoplasm and evidence of local invasion. To the best of our knowledge, extrahepatic bile duct carcinomas have not been described in cattle.